2017
DOI: 10.12669/pjms.334.13045
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of prevalence and comorbidity of obsessive compulsive disorder symptoms (SOCD) and stress in Pakistani Adults

Abstract: Objective:To investigate the prevalence and comorbidity of subclinical obsessive compulsive disorder (SOCD) symptoms and stress across gender, marital and employment statuses.Methods:A cross-sectional research was conducted from December, 2016 to March 2017 at two universities of cosmopolitan city Lahore. Two self-report scales measuring SOCD symptoms and stress were used to collect data from 377 adults selected through simple random sampling technique, proportionately distributed across gender, marital and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…There is no significant difference (p = 0.80 and p = 0.57) between marital status and COVID compulsive checking, respectively (8). There is a significant incidence of OCD in unmarried individuals, which is in line with previous research that suggests single people are more likely to be affected than married people (9). The Obsessive-compulsive symptoms were seen in 18.5 percent of the participants (n = 37/200).…”
Section: Discussionsupporting
confidence: 84%
“…There is no significant difference (p = 0.80 and p = 0.57) between marital status and COVID compulsive checking, respectively (8). There is a significant incidence of OCD in unmarried individuals, which is in line with previous research that suggests single people are more likely to be affected than married people (9). The Obsessive-compulsive symptoms were seen in 18.5 percent of the participants (n = 37/200).…”
Section: Discussionsupporting
confidence: 84%
“…Previous research suggested inconsistent findings. While some studies demonstrated that posttraumatic stress levels in females were statistically significantly higher than in males (Lehavot et al, 2018;Ashraf et al, 2019;Xue et al, 2015;Baştuğ & Aslantaş, 2021;Kilpatrick et al, 2000;Ünver & Karakaya, 2019;Trickey et al, 2012;Karalalı, 2021); some other found no significant difference between females' and males' post-traumatic stress levels (Bulut, 2009;Liv et al, 2016;Kar et al, 2006). Olff (2017) oxytocin levels are higher, and females face more high-impact traumas (e.g., sexual trauma) than males during their lifetime.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…A study found that PTSD increases women’s BMI and obesity rates after childhood trauma (Dedert et al, 2010). A physical injury combined with a traumatic event increases the risk of developing post-traumatic stress disorder, which affects the subjective impression of physical health, such as somatoform and psychosomatic diseases and post-concussion syndrome (Auxéméry, 2018). Recent research links PTSD to cardiovascular disease vulnerability (Krantz et al, 2021).…”
Section: Effects Of Ptsd On Womenmentioning
confidence: 99%
“…Also, young girls who endure trauma or maltreatment in childhood, such as sexual assault or domestic violence, have a much-increased chance of having PTSD as adults (Gobin et al, 2013, Kessler et al, 1995. According to the study by Ashraf et al (2019), females scored higher on PTSD symptoms than males, and this was connected with childhood maltreatment.…”
Section: Symptoms Of Ptsdmentioning
confidence: 99%